MicroRNA‐155 modulates P2R signaling and Th2 priming of dendritic cells during allergic airway inflammation in mice. Issue 9 (28th May 2015) - Zech, A.; Ayata, C. K.; Pankratz, F.; Meyer, A.; Baudiß, K.; Cicko, S.; Yegutkin, G. G.; Grundmann, S.; Idzko, M.
Abstract Background Dendritic cells (DCs) are the professional antigen‐presenting cells (APCs) in the lung. They are known to be key players in the induction and maintenance of allergic asthma by cross‐linking innate and adaptive immune responses. MicroRNAs (miRNAs) are known to influence cell fate and function by translational suppression or induction of messenger RNA (mRNA) degradation. miR‐155 has been shown to be a crucial regulator of the immune system. However, its function in the pathogenesis of allergic airway inflammation (AAI) is not completely elucidated yet. Methods Wild type (WT) and miR‐155‐deficient (miR‐155−/−) mice were used in ovalbumin (OVA) and house dust mite (HDM) models of AAI. Adoptive transfer of sensitized DCs to the lungs, migration, and T‐cell priming assays were used to investigate the functional relevance of miR‐155 in DCs. Results miR‐155−/− mice showed reduced eosinophilic airway inflammation compared to WT mice in both models of AAI. Furthermore, miR‐155−/− DCs showed limited Th2 priming capacity and failed to induce airway inflammation in allergen‐exposed WT mice. miR‐155 deficiency on DCs was also associated with impaired purinergic receptor signaling, as miR‐155‐/‐ DCs showed reduced chemotaxis and IL‐1beta secretion upon stimulation with ATP, probably due to direct targeting of ectonucleoside triphosphate diphosphohydrolases (ENTPD) by miR‐155. Conclusions miR‐155 deficiency alleviates AAI by diminishing Th2 priming capacity and ATP‐/P2R‐induced activation of DCs in mice, suggesting this miRNA as a potential therapeutic target of AAI.